Microstructural white matter changes of covert stroke and its neurological impact in non-cardiac surgery patient - Cheah, Wai Hun (2018)
Objectives: The objective of the study is to study the whole brain microstructural white matter integrity changes occurring in peri operative covert stroke at acute and chronic stage (as determined by diffusion tensor imaging i.e. fractional anisotropy (FA), mean diffusivity (MD), radial diffusivity (RD) and axial diffusiviry (AD) values). Secondary objectives are to detect the white matter microstructural integrity changes occurring in perioperative stroke along the changes with Montreal Cognitive Assessment (MOCA) at acute and chronic stage. Method: Over a period of two and balfyears, 16 patients who underwent non-cardiac surgery and 14 age match control were recruited for this study. Montreal Cognitive Assessment (MOCA) score and I.S T MRl brain scan were done within two weeks of operation and one-year post surgery to look for stroke and microstructural changes. Results: S patients develop perioperative covert stroke (PCSa). In the acute period, PCSa patients and peri-operative non stroke patients (PNSa) have significantly lower median score (p< O.OS) in MOCA compared to control in these following domains: visual-spatial (pCS:4 vs. PNSa:S vs. control:S), attention (PCS:6 vs. PNSa:S vs. control:S), language (PCS: I vs. P Sa:2 vs. control:3) and delayed recalled (PCS:2 vs. PNSa:4 vs. control:S). PCSa patients demonstrates S tracts showing decrease in FA with increase in MD and RD, two of which showed increase in AD as well. These tracts are right posterior thalamic radiation, left posterior thalamic radiation, right cingulum, left cingulum and right fornix. After one year follow-up, left and right posterior thalamic radiation shows improvement ofDTI indices in PCS. The rest of three tracts, i.e. right cingulum, left cingulum and right fornix showed no significant changes as compared to controls. Conclusion: This study shows perioperative patients (PCSa and PNSa) in acute period, have a lower MOCA scoring then control. DTI detects microstructural changes occurring in perioperative stroke along the changes with MOCA. The perioperative stroke in non-cardiac surgery however, does not have a long-term progression in terms ofneurocognitive or microstructural changes. Keywords: DTI, FA, MOCA, peri-operative stroke.